EXPLORING EFFECTIVE ENGLISH TEACHING APPROACHES FOR CUSTOMS PROFESSIONALS: INSIGHTS FROM QUESTIONNAIRE-BASED RESEARCH (Journal of Universal Science Research, 2025)
This study examines effective approaches to teaching the English language that are specifically designed to meet the professional requirements of customs officers. Acknowledging the critical role of English in international communication, trade facilitation, and border management, the research evaluates the alignment of existing teaching methodologies with the practical language needs of customs professionals. Utilizing data collected through questionnaires distributed to Customs institute cadets, the study identifies the most effective teaching strategies, prevalent challenges in language training, and potential areas for enhancement. The results underscore the significance of context-specific, communicative, and task-oriented approaches, providing actionable recommendations for the development of English for Specific Purposes programs within customs training organizations.